Supervision of Mining Businesses in the Environment Service in North Morowali Regency - Fajrin, Miftahu; Rivai, Abdul; Nurhannis, Nurhannis (CV RIFAINSTITUT, 2025)
This study aims to find out the form of supervision of the Environment Agency over mining activities in North Morowali Regency, especially on the environmental impact caused by mining activities in Bahoue Village. The background of this research is based on various environmental problems such as floods, forest destruction, air pollution, and social conflicts that occur between communities and mining companies. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study show that the supervision carried out by the Environment Agency is still not optimal. This can be seen from the many violations committed by mining companies, such as not having a waste disposal permit, lack of B3 waste management facilities, and the absence of adequate reclamation actions. In addition, weak supervision also has an impact on increasing environmental damage and public dissatisfaction. Therefore, this study recommends strengthening the supervisory function, increasing human resource capacity, and strictly enforcing environmental laws to realize sustainable and equitable mining governance